Migration of the highly skilled: Can Europe catch up with the US? - Lydia Mechtenberg; Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
We develop a model to analyze the determinants and effects of an endogenous imperfect transferability of human capital on natives and immigrants. The model reveals that high migration flows and high skill-transferability are mutually interdependent. Moreover, we show that high mobility within a Federation is necessary to attract highly skilled immigrants into the Federation. We study in how far and in what way the European public policy behind the Bologna and the Lisbon Process can contribute to higher mobility in Europe.
Keywords: D61; H77; I28; 330; human capital; migration; transferability; public policy; Brain Drain; Wissenstransfer; Hochqualifizierte Arbeitskräfte; Internationale Arbeitsmobilität; EU-Bildungspolitik; Lissabon Strategie; EU-Staaten